success and failure rates of orthodontic microimplants (Aclinical study) - Ahmad A Abdulmawjood; Mahmood Kh Ahmad; Zaid S Tawfiq (University of Mosul, College of Dentistry, 2011)
Aims: To evaluate the rates of success and failure regarding the mobility of orthodontic microimplants in patients undergoing fixed orthodontic appliance treatment. Materials and Methods: The sample consisted of 36 titanium microimplants (AbsoAnchor®, Dentos inc. Korea) inserted in 15 female patients. The mean age for the patients was 25.53 years. Microimplants of 1.2 mm in diameter and 6-10 mm in length were used. A self-drilling method was used. A small vertical stab incision and the microimplants inserted with a screwdriver. The patients were seen periodically every 3-4 weeks. A microimplant with complete absence of a clinically detectable mobility was considered as a successful one. Whereas failure was defined as a microimplant mobility within 8 months. Results and Discussion: The total success rate for microimplants for both jaws was (86.1%). Whereas a (91.7%) success rate was recorded in the upper jaw and in the lower jaw it was (75%). Despite of higher failure rates in the mandible, which may be attributed to the occlusal force, yet they remain non significantly different from those in maxilla. Conclusions: The relatively high success rates of microimplants make them an appropriate solution for providing absolute anchorage whenever being needed in orthodontic therapy